Le suprême hommage De omgang met de dood van koninklijke en politieke elites in België tussen 1830 en 1940 - De Spiegeleer, Christoph (ASP editions - Academic and Scientific Publishers, 2020)
Le suprême hommage studies the handling of dying, burial and commemoration of royal and political elites in Belgium in the 19th and first half of the 20th century. This innovative historical research takes place at the interface of cultural history and political history. The reader not only gains insight into the impact of social class, status and religion on funerary culture, but also into the influence of media culture on the perception of death, mourning and memory. Within a selection of 170 cases, the author discusses in words and images the mediatised deaths and no less than imposing funerals of Belgium's first kings and queens and their families. The evolving practices surrounding the deaths of (former) heads of government, (former) presidents of parliament and mayors of major cities are also discussed in detail. Finally, the genesis of Belgium's most famous urban (park) cemeteries, and the funerary heritage in these cities of death, is also brought to life through the analysis of eye-catching funeral monuments. This book is a richly illustrated survey work on the social, political and cultural dimensions of the death of high-ranking figures in 19th- and 20th-century Belgian society.